Pyridinium-based ionic liquids as anti-wear additives for calcium sulfonate greases - Nikita Semenov; Nikolay Pugachev; Anna Peskovets (Tribology and Materials)
The present study showed the usage of ionic liquids as anti-wear additives for greases. New pyridinium-based ionic liquids bearing long alkyl chains were prepared and evaluated as wear-reducing additives in calcium sulfonate greases. The physical properties of the synthetic ionic liquids were identified. The obtained liquids were then added to greases at a concentration of 2 wt. %. The tribological performance of the greases was measured by using a standard benchtop test ASTM D2266. The results obtained allow us to conclude that the introduction of ionic liquids into polyalkylene glycol (PAG)-based calcium sulfonate grease has a positive effect on anti-wear properties since the wear decreases by several orders of magnitude. The interoperability of the synthetic ionic liquids with the calcium sulfonate greases and its potential influence upon solubility and tribological performance are tentatively proposed to be a result of the molecular structure.